3-dimensional environmental contours based on a direct sampling method for structural reliability analysis of ships and offshore structures. (2nd January 2019) - Vanem, Erik
ABSTRACT: This paper derives a simple way of calculating 3-dimensional environmental contours for structural reliability assessment and design of ships and offshore structures. The 3-dimensional contours are based on Monte Carlo sampling from the joint distribution of the input parameters for response calculations and are an extension of previously proposed 2-dimensional contours. The 3-dimensional contours offers a practical way of identifying multivariate joint extremes of relevant input variables in order to provide for analyses of extreme structural responses. The contour estimation method is applied to some simple example cases and is demonstrated to work well and give reasonable results. Hence, the 3-dimensional contours represent a practical tool for anyone involved in probabilistic structural reliability analysis and design of ships and offshore structures.